2022
DOI: 10.1002/ctm2.881
|View full text |Cite
|
Sign up to set email alerts
|

FL118, acting as a ‘molecular glue degrader’, binds to, dephosphorylates and degrades the oncoprotein DDX5 (p68) to control c‐Myc, survivin and mutant Kras against colorectal and pancreatic cancer with high efficacy

Abstract: By acting as a 'molecular glue degrader', FL118 directly binds to and functionally dephosphorylates and degrades the multifunctional master regulator DDX5 through the proteasome degradation pathway without decreasing DDX5 mRNA.• FL118 indirectly controls DDX5 downstream targets to inhibit cancer initiation, development, metastasis, recurrence and treatment resistance with high efficacy as demonstrated in this study using human colorectal cancer/pancreatic ductal adenocarcinoma cell and tumour models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 89 publications
(201 reference statements)
2
37
0
Order By: Relevance
“…In this regard, using the small-molecule drug FL118 affinity column purification of cancer cell lysate proteins, followed by mass spectrometry analyses, Ling et al identified that the DDX5 protein is the direct biochemical target of FL118. These authors demonstrated that FL118 acting as an MG degrader strongly binds to, dephosphorylates, and degrades DDX5 oncoprotein via proteasome degradation pathway, without decreasing DDX5 mRNA [ 49 ]. These studies further revealed that DDX5 is a master regulator for controlling the expression of multiple oncogenic proteins including survivin, Mcl-1, XIAP, cIAP2, c-Myc, and mutant Kras (mKras) [ 49 ].…”
Section: Molecular Glues For Cancer Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…In this regard, using the small-molecule drug FL118 affinity column purification of cancer cell lysate proteins, followed by mass spectrometry analyses, Ling et al identified that the DDX5 protein is the direct biochemical target of FL118. These authors demonstrated that FL118 acting as an MG degrader strongly binds to, dephosphorylates, and degrades DDX5 oncoprotein via proteasome degradation pathway, without decreasing DDX5 mRNA [ 49 ]. These studies further revealed that DDX5 is a master regulator for controlling the expression of multiple oncogenic proteins including survivin, Mcl-1, XIAP, cIAP2, c-Myc, and mutant Kras (mKras) [ 49 ].…”
Section: Molecular Glues For Cancer Treatmentmentioning
confidence: 99%
“…These authors demonstrated that FL118 acting as an MG degrader strongly binds to, dephosphorylates, and degrades DDX5 oncoprotein via proteasome degradation pathway, without decreasing DDX5 mRNA [ 49 ]. These studies further revealed that DDX5 is a master regulator for controlling the expression of multiple oncogenic proteins including survivin, Mcl-1, XIAP, cIAP2, c-Myc, and mutant Kras (mKras) [ 49 ]. Pancreatic ductal adenocarcinoma (PDAC) cells with DDX5 knockout by vector-free Crispr technology are resistant to FL118 treatment [ 49 ], indicating DDX5 is a bona fide FL118 target.…”
Section: Molecular Glues For Cancer Treatmentmentioning
confidence: 99%
See 3 more Smart Citations